Big Five Personality Traits and Reciprocal Relationship between Job Satisfaction and Job Performance - Liany Halim; Rhian Indradewa; Tantri Yanuar Rahmat Syah (Penerbit Kemala Indonesia, 2020)
This study aims to connecting the relationship between three variables related to human resource management in a company namely personality traits, job satisfaction and job performance. This model was developed to build a hypothesis on how personality can increase job satisfaction and job performance and influence between job satisfaction and job performance. The survey was conducted from October 2019 to January 2020 through a Google form survey. Here, the 485 data were collected from correspondents which were then validated. In this study, we are using LISREL 8.7 to develop the model values. In addition, this study is contributing to add the findings compilation of clarify inconsistencies in previous findings between relationship of personality characteristics that most influence with job satisfaction and performance.